The (un)acceptable liberalisation of the (welfare) state - Zalar, Boštjan (Družboslovne razprave, 1999)
Any state liberalisation policy is justified to the extent that expectations of reform broadening the chances of all individuals for the better realisation of their human rights (including rights with what is termed positive status') are reasonable. In order to fulfill this premise, justice should be combined with freedom and equality as the third basic and obligatory principle of social regulation. This standard, together with some functional conditions for liberalisation within the social services sector, leads to the conclusion that the state need not be the owner of social services. However, it is necessary that state officials exercise permanent and strict control over both the impact of liberalisation processes and the practice of social services in the private sector on all three basic regulatory principles. This premise is also highly relevant for the liberalisation processes within the executive and judicial branches of government, where special attention must be given to the maintenance of the state monopoly over the repression mechanism. The author concludes by advocating a new development paradigm which favors and connects the liberalisation of the external world with the privatisation of self.
Keywords: država; state; welfare state; socialna država; država blaginje; liberalizacija; privatizacija; lastnina; človekove pravice; human rights